Community Empowerment Against Efforts to Prevent the Transmission of the Covid-19 Virus Through Socialization of The Implementation of the 3M Movement at the University of Muhammadiyah North Maluku Campus - Hairudin La Patilaiya; Ranita Rope; Hamidah Rahman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The COVID-19 pandemic is an event of the spread of Coronavirus Disease 2019 (English: Coronavirus disease 2019, abbreviated as COVID-19) throughout the world for all countries. This disease is caused by a new type of corona virus called SARS-CoV-2. The COVID-19 outbreak was first detected in Wuhan City, Hubei, China on December 1, 2019, and was designated a pandemic by the World Health Organization (WHO) on March 11, 2020. The purpose of IbM activities is to increase community participation in preventing transmission of Covid-19 through the application of the 3M movement. The method of this activity is to visit residents' homes, lectures, questions and answers, FGDs and assistive devices, namely laptops, stickers, posters and masks by involving the community, namely the campus community (Fikes students), the Gambesi Village community and the Sasa village community. The results of the IbM activity are (1) the public can understand the application of the 3M movement to prevent the transmission of covid-19. (2) the public realizes that the application of 3M can reduce the risk of transmission of covid-19. With the implementation of the IbM activity, it can be concluded that the public has a higher understanding and awareness of the efforts to implement the 3M movement to prevent the spread of the Covid-19 virus on the North Maluku Muhammadiyah University campus. From IbM activities, it is suggested to the public to always apply health protocols through the 3M movement, namely wearing masks, washing hands and keeping a distance when doing activities.